Key drivers and priorities of consumer decisions for refurbished electronics: A mix-method approach - Barkhi, Fatemeh; Ahmadi, Sadra; Shokouhyar, Sajad; Filieri, Raffaele; Ramezaninia, Masoud (Heliyon, 2024)
Product refurbishment enhances waste minimization and environmental sustainability. However, the sale of these products relies on consumer attitudes, influenced by various factors. This study adopts a novel mixed-methods approach, utilizing structural and network analysis based on over 60,000 comments and tweets from X.com (formerly Twitter), complemented by insights from expert interviews, to analyze factors affecting consumers viewpoints when making decisions about purchasing refurbished electronics. The research identifies and prioritizes 17 key influencing factors, highlighting the interplay between large-scale consumer sentiment and expert opinions. A customer-centric purchase decision model is presented, showing that consumer priorities when purchasing refurbished products typically revolve around retailer reputation, brand, pricing, warranty, and product quality. These findings offer valuable guidance for producers on how to target higher-priority consumer concerns, ultimately helping to expand their market and boost purchasing intention.